Dopamine D2 receptor agonist, bromocriptine, remodels adipose tissue dopaminergic signalling and upregulates catabolic pathways, improving metabolic profile in type 2 diabetes - Tavares, G. (2021)
Funding: We thank to the at Laboratório de Biomedicina Mitocondrial e Teranóstica, Centro de Neurociências e Biologia Celular for the assistance with RNA integrity analysis. We thank the Serviço de Anatomia Patológica, Coimbra University Hospital, especially Ilda Simões, for the support with histological techniques. This work was supported by a grant from GIFT (Grupo de Investigação Fundamental e Translacional) from the Portugal Society of Diabetes and Portugal Foundation for Science and Technology (PEst UID/NEU/04539/2013 and UID/NEU/04539/2019: CNC.IBILI; PEst UIDB/04539/2020 and UIDP/04539/2020: CIBB). G.T and B.F.M. were supported by PhD Grants from the Portuguese Foundation for Science and Technology (PD/BD/127822/2016 and PD/BD/128336/2017, respectively). Bromocriptine was kindly provided by Generis Portugal.